Передісторія виникнення і формування української мемуарно-автобіографічної літератури - Черкашина, Тетяна; Cherkashyna, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2014)
Статтю присвячено вивченню передісторії зародження української мемуарно-автобіографічної літератури. Проаналізовано вітчизняні спогадові твори ХІІ–ХVIII ст., увагу звернено на те, що вони здебільшого мали синкретичний характер без яскраво виражених жанрових характеристик./ The article is devoted to the study of the ancient Ukrainian memoirs-autobiographical literary works. The author of the article analyses the Ukrainian self-writing of the XII–XVIII centuries created by Volodymyr Monomakh, Stanyslav Orikhovskyi (Roksolan), Illia Turchynovskyi, Hryhorii Galahan, Vasyl Zahorovskyi, Matvei Stryikovskyi, and Vasyl Hryhorovych-Barskyi. The Ukrainian memoirs-autobiobraphical tradition of that time was presented the spiritual autobiographies. Apologetics, representation of autobiographer’s spiritual and religious evolution, motive of the saving divine force were the main features of that works. The widespread tradition was insertion of memoirs and autobiographical components in the other literary genres such as homily, letter, testament, travelogue, and others. The author of the article establishes that the Ukrainian self-writing of the XII–XVIII centuries didn’t have the systematical character but its works became the beginnings of the Ukrainian memoirs-autobiographical tradition.
The Prehistory of Beginnings and Formation of the Ukrainian Memoirs-autobio¬graphical Literature
Черкашина Т. Передісторія виникнення і формування української мемуарно-автобіографічної літератури / Тетяна Черкашина // Науковий вісник Східноєвропейського національного університету. Сер. «Філологічні науки. Літературознавство». – 2014. – № 9 (286). – С. 146-151.
Keywords: мемуарно-автобіографічна література; автобіографія; духовна автобіографія; дискретна автобіографія; спогади; memoirs-autobiographical literature; autobiography; spiritual autobiography; discrete autobiography; reminiscences